The role of Zr and T6 heat treatment on microstructure evolution and hardness of AlSi9Cu3(Fe) diecasting alloy - Vončina M.; Kores S.; Ernecl M.; Medved J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The microstructure features and hardness of AlSi9Cu3(Fe) die casting alloy was investigated in the presence of Zr addition. The cast alloys were undergone the solutionizing treatment 2 h at 500°C followed by artificial aging at 180°C for 5 h. Optical microscopy and electron micro-analyzer were used to study the formation of different intermetallic phases. The hardness was tested for all samples at 25°C. The results revealed that the intermetallic phase, based on (Al,Si)(Zr,Ti), forms when Zr is added in the investigated alloy, while the T6 heat treatment does not influence on the formation of Zr-bearing phase. Results also indicate that the hardness slightly increases in the AlSi9Cu3 alloy in as-cast state when Zr is added, while after T6 heat treatment increases by 50% in the alloy without Zr and by 61% in the alloy with Zr addition.